Ethnic Heterogeneity of the Factor XIII Val34Leu Polymorphism - Attié-Castro, Flávia A.; Zago, Marco A.; Lavinha, João; Elion, J.; Rodriguez-Delfin, L.; F.Guerreiro, João; Franco, Rendrik F. (Thrombosis and Haemostasis, 2000)
A polymorphism in the coagulation factor XIII gene (FXIII Val34Leu) has been recently described to confer protection for arterial and venous thrombosis and to predispose to intracerebral hemorrhage. At present it is known that FXIII Val34Leu is prevalent in Caucasians, but information upon its distribution in different ethnic groups is scarce. We investigated the prevalence of FXIIIVal34Leu in 450 unrelated subjects of four ethnic groups: 97 Caucasians (Brazilians of European descent and Portuguese), 149 Blacks (Brazilians, and Africans from Cameroon, Zaire and Angola), 40 Asians (Japanese descendents) and 164 Amerindians from South America. PCR amplification of exon 2 of FXIII gene followed by MseI restriction-digestion was employed to define the genotypes. FXIIIVal34Leu was detected in 44.3% of the Caucasians, in 28.9% of the Blacks, in 2.5% of the Asians and in 51.2% of the Amerindians. These data confirm that FXIII Val34Leu is highly prevalent in Caucasians and indicate that it is rarer in populations of African origin. The very high frequency among Amerindians indicates that FXIII Val34Leu is not absent among Asians, and since it has a very low prevalence in Japanese, a heterogeneity in its distribution in Asia may be inferred. Taken together, our data showed that FXIII Val34Leu exhibits a significant ethnic heterogeneity, a finding that is relevant for studies relating this polymorphism with thrombotic and bleeding disorders.
Keywords: Factor XIII; ethnic groups; thrombosis; risk factor